The Preference of Chinese Tourists in Choosing Accommodation in Badung Regency - Agung Sri Sulistyawat; Fanny Maharani Suarka (Journal of Business on Hospitality and Tourism, 2020)
This study determines the characteristics and preferences of Chinese tourists in choosing accommodations in Badung district. Based on the Bali Central Bureau of Statistics 2016-2018, there is an increase of Chinese tourists' visits to Badung Regency, mainly Nusa Dua, Kuta and Jimbaran famous for its tourist destination accommodations thus makes it highly competitive. This study consists of 50 Chinese tourists as respondents using questionnaires from May-July 2019 selected by incidental sampling, then analyzed by conjoint technique which revealed that most prefer the Nusa Dua area. Characteristically most of them come from Liaoning Province dominated by women aged 15-24 years. Eighty six per cent of these are private employees with a bachelor's degree. It is their first visit to Badung Regency with an average length of stay of 4-6 days accompanied by friends for leisure activities. They obtain information from the internet and 92% of them chose a star rated accommodation.Tourist preferences in accommodation selection are analyzed and summarised as important values. The resulting highest to lowest values are as follows: facilities, Promotion, comfort, location, service, price, and cleanliness.